2019
DOI: 10.3389/fpsyt.2019.00340
|View full text |Cite|
|
Sign up to set email alerts
|

Preventing and Reducing Coercive Measures—An Evaluation of the Implementation of the Safewards Model in Two Locked Wards in Germany

Abstract: Introduction Aggression and violence are highly complex problems in acute psychiatry that often lead to the coercive interventions. The Safewards Model is an evidence-informed conflict-reduction strategy to prevent and reduce such incidents. The aim of this study was to evaluate the implementation of this model with regard to coercive interventions in inpatient care. Materials and Methods We evaluated outcomes of the implementation of the Safewards Model in two locked p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
158
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(167 citation statements)
references
References 50 publications
(76 reference statements)
1
158
0
7
Order By: Relevance
“…Previous research has reported significantly different ratings between staff and patients on climate measures (Baumgardt et al, 2019; Berry et al, 2016; Moos, 1974; Nicholls et al, 2015; Southard et al (2012); ; ; ; ; ; ; ; . While the literature is not without inconsistencies, the weight of evidence across settings and measures is that, relative to patients, staff overestimate their own abilities as active agents for therapeutic change and that patients, relative to staff, perceive a greater role for themselves in determining ward climate.…”
Section: Methodsmentioning
confidence: 97%
“…Previous research has reported significantly different ratings between staff and patients on climate measures (Baumgardt et al, 2019; Berry et al, 2016; Moos, 1974; Nicholls et al, 2015; Southard et al (2012); ; ; ; ; ; ; ; . While the literature is not without inconsistencies, the weight of evidence across settings and measures is that, relative to patients, staff overestimate their own abilities as active agents for therapeutic change and that patients, relative to staff, perceive a greater role for themselves in determining ward climate.…”
Section: Methodsmentioning
confidence: 97%
“…Future work on necessary components for an early intervention psychosis clinic as well as cost benefit analyses of such a program are recommended [13,22,49,50]. It is also known and often observed that psychotic disorders tend to present with aggression and violence injuring staff and fellow patients [51,52]. Acute psychiatric units or psychiatric intensive care units have been shown to be especially effective in containing such potentially dangerous behaviour [51], hence calling for such care facilities as useful additions to mental hospitals as opposed to just locked seclusion rooms as is the practice at this facility [51,52].…”
Section: Mental Health Service Requirements For Patients With Psychotmentioning
confidence: 99%
“…Future work on necessary components for an early intervention psychosis clinic as well as cost benefit analyses of such a program are recommended (13, 21, 42, 43). It is also known and often observed that psychotic disorders tend to present with aggression and violence injuring staff and fellow patients (44, 45). Acute psychiatric units or psychiatric intensive care units have been shown to be especially effective in containing such potentially dangerous behaviour (44), hence calling for such care facilities as useful additions to mental hospitals as opposed to just locked seclusion rooms as is the practice at this facility (44, 45).…”
Section: Discussionmentioning
confidence: 99%